ANALISIS KEMAMPUAN PUBLIC SPEAKING GURU DI SD INPRES BONE KECAMATAN BAJENG KABUPATEN GOWA - Amiluddin, Nurhikmah; Bahri, Aliem; Ratnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the public speaking skills of elementary school teachers as a key factor in supporting effective classroom learning. Teachers, as primary communicators, are required to deliver instructional material clearly, engagingly, and comprehensibly; however, variations in verbal and nonverbal communication skills are still evident. This research aims to analyze the public speaking skills of teachers at SD Inpres Bone, Bajeng District, Gowa Regency. A qualitative approach with a descriptive design was employed. Data were collected through classroom observations, audio and video recordings, interviews, and documentation. Observations and recordings were conducted to capture real teaching practices, while interviews provided in-depth insights into teachers’ experiences and communication challenges. The data sources included teachers from grades 1 to 6 to obtain a comprehensive overview. The findings reveal that teachers generally demonstrate good intonation by varying pitch effectively, although assertive tones tend to dominate. In terms of vocal aspects, most teachers have clear and adequately loud voices with stable speech tempo, facilitating student understanding. Word choice is generally simple and appropriate to students’ developmental levels, despite the frequent use of directive sentences. Gestures are used in classroom management but are not yet optimal in reinforcing instructional content. Facial expressions are mostly positive and supportive, contributing to a conducive learning environment. Overall, teachers’ public speaking skills are adequate, yet several aspects still require improvement to enhance instructional communication effectiveness and expressiveness.